Land cover changes through ESA-CCI-LC maps (2000-2015) in Ixtacamaxtitlán, Puebla - Arroyo-Ortega, Itzel; Tamaríz-Flores, Víctor; Torres-Ramírez, Eduardo; Handal-Silva, Anabella; Chávez-Bravo, Edith; Cervantes-Gutiérrez, Virginia; Castelán Vega, Rosalía (Instituto de Ecología, A.C., 2021)
The determination of Land Cover (LC) changes is important to understand ecosystem dynamics. In this study, spatial-temporal changes were analyzed in the municipality of Ixtacamaxtitlán, Puebla during the period 2000-2015 using European Space Agency (ESA) Climate Change Initiative Land Cover (CCI-LC) global maps. For this purpose, the change matrix, the annual change rate, and the permanence probability were determined, as well as the accuracy of the LC 2015 map. The results show that losses were observed in forests and grasslands (0.27% and 8.83%, respectively), while gains occurred in croplands and urban areas (6.9% and 8.11%, respectively). Most of the changes were observed in the easy-access areas located in the north-central portion of the municipality. Of the 1962 ha that showed changes between categories, 87.4% was negative and 12.6% was positive, highlighting the transition from grasslands and forest lands to cropland, caused by various socio-economic processes in the area such as marginalization, migration, access to government programs, expansion of agricultural areas and crop diversification. The map of LC 2015 showed a high precision at the subnational level (85.64%) which reveals that this data set is reliable for the study of the transformations in the territory.